Pekerja Imigran Perempuan dalam Perspektif Islam - Kelik Wardiono; Wafda Vivid Izziyana (ISTAWA, 2019)
Islamic law gives a high appreciation for the human equality. It happens because all humans come from one source, Allah S.W.T. Respecting of human rights is regulated in fiqih, holy Qur’an, and hadist. From the Islamic law perspective, the differentiate of human level is on their devotion. Working as a migrant worker is allowed in Islamic Law. State gives regulation for the Indonesian migrant in a constitution No 18, 2017 year. The constitution is provide to give all society to have work both of domestic and overseas with a certain period, of course they get salary. Working is a citizen’s right. The purpose of migrant is to get bigger result. Other factor which triggers the Indonesian citizen of Indonesia to change the fate is the difficulty of getting work. There are many kinds of work in this country. Various job opportunities that exist in this country but most of them have been occupied by Indonesian society. Consequently, it is being minimum opportunity for the next generation. Indonesian mindset of working abroad to be a migrant worker is a necessity. The real fact is when women work, and then they have to perform two roles, as a wife or a mother as well as a worker.  This article will discuss about the female position as a migrant viewed from the religion point of view, especially in term of Islamic law related to Indonesian female migrant workers.